2019
DOI: 10.1002/14651858.cd003814.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for replacing missing teeth: partially absent dentition

Abstract: Interventions for replacing missing teeth: partially absent dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 83 publications
1
7
0
1
Order By: Relevance
“…To answer the first clinical question (CQ#1), this systematic review identified two RCTs and one non‐RCT on comparison of OHRQoL between SDA and RPDP restorations. Narrative appraisal and meta‐analysis of these studies did not reveal RPDP restoration of missing molars as being superior to SDAs with intact premolar occlusion in terms of OHRQoL, which corresponds with the conclusions of previous reviews that supported clinical application of the SDA concept . Considering that perceived need for dental treatment is associated with OHRQoL impairment , the conclusions drawn from these systematic reviews justify the concept that patients with SDA do not need additional prosthodontic treatment.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…To answer the first clinical question (CQ#1), this systematic review identified two RCTs and one non‐RCT on comparison of OHRQoL between SDA and RPDP restorations. Narrative appraisal and meta‐analysis of these studies did not reveal RPDP restoration of missing molars as being superior to SDAs with intact premolar occlusion in terms of OHRQoL, which corresponds with the conclusions of previous reviews that supported clinical application of the SDA concept . Considering that perceived need for dental treatment is associated with OHRQoL impairment , the conclusions drawn from these systematic reviews justify the concept that patients with SDA do not need additional prosthodontic treatment.…”
Section: Discussionsupporting
confidence: 79%
“…They, consequently, failed to provide strong evidence that could potentially impact clinical decision‐making . In 2012, the Cochrane Library published a systematic review including only RCTs . However, because only one relevant RCT with respect to OHRQoL could be identified at the time of literature search, this review did not involve meta‐analysis.…”
Section: Introductionmentioning
confidence: 99%
“…53 Furthermore, a Cochrane systematic review on interventions for the partially absent dentition identified only 5 trials evaluating RPDs for inclusion. 1 Three of the trials evaluated different aspects of RPD design, [54][55][56] one trial evaluated different materials used in RPDs, 57 and another compared different fabrication techniques. 58 It can be concluded that there is a shortage of clinical trial data on RPDs, leading to a lack of evidence.…”
Section: Researchmentioning
confidence: 99%
“…[44] Missing teeth *CP The condition in which diagnosis of missing teeth has been made by a dentist. [45] Crown fracture *CP The condition in which diagnosis of crown fracture has been made by a dentist. [42] Ill-fitting prosthesis *CP The condition in which diagnosis of ill-fitting prosthesis has been made by a dentist.…”
Section: Impaired Verbal Communicationmentioning
confidence: 99%